Legal Review of Copyright as Fiduciary Guarantee on Credit Agreements in Sharia Banking Financial Institutions - Gama Bhakti, Indira Swasti; Ramadhani, Mutiara; Puspandari, Rr. Yunita; Prabowo, Wahyu (Universitas Muhammadiyah Surakarta, 2024)
Copyright certificates for songs can be an object of fiduciary collateral in baking making it easier for creative economy actors to obtain credit. The problem of this research is what are the legal aspects of using copyright certificates as fiduciary collateral in credit agreements and what is the legal protection of banking financial institutions against the execution process. The aim and benefit of this research is to determine the legal aspects of using copyright certificates as fiduciary collateral in credit agreements and the protection of banking financial legal institutions against the execution process. This research method uses normative juridical research which uses a legal and conceptualization approach with data collection methods from literature studies and interviews. Based on research results, banking financial institutions have not accepted copyright certificates as objects of fiduciary collateral because they did not receive socialization from the central bank and weakened copytight market segmentation, making it difficult for the execution process when debtors default. Therefore, the use of copyright certificates in banking refers to the Fiduciary Guarantee Law, Copyright Law, Creative Economy Law and Creative Economy PP and the existence of legal protection, both preventive, namely in collaboration with LMKN and repressive through litigation and non-litigation against banks, is expected to be able to reduce risk and make it easier for banks to carry out the executions process when debtors default.